2015
DOI: 10.1186/s12876-015-0404-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Non-Alcoholic Fatty Pancreas Disease (NAFPD) and its risk factors among adult medical check-up patients in a private hospital: a large cross sectional study

Abstract: BackgroundThe clinical significance of non-alcoholic fatty pancreatic disease (NAFPD) or fatty pancreas is largely unknown. It is often an incidental finding on abdominal ultrasound, which is not explored further, especially its association with metabolic condition and the risk of pancreatic malignancy. The aim of this study is to evaluate the presence of NAFPD and its associated risk factors among adult medical check-up patients.MethodA large cross-sectional study was done among adult medical check-up patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 18 publications
5
93
1
8
Order By: Relevance
“…These sex‐specific differences may be one reason that various population‐level studies including both men and women have found only modest trends relating Panc‐LC with other variables. Taken together, our data suggest that BMI and age play a sex‐specific role in pancreatic steatosis, which has been reported in only a few prior imaging studies . Additionally, we found a significant correlation between Panc‐LC and Islet‐LC, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…These sex‐specific differences may be one reason that various population‐level studies including both men and women have found only modest trends relating Panc‐LC with other variables. Taken together, our data suggest that BMI and age play a sex‐specific role in pancreatic steatosis, which has been reported in only a few prior imaging studies . Additionally, we found a significant correlation between Panc‐LC and Islet‐LC, which has not previously been reported.…”
Section: Discussionsupporting
confidence: 78%
“…To complicate this, some studies also incorrectly include accumulated visceral fat around the exterior of the organ in their measurements, either due to technical difficulty to distinguish or by ambiguous definition of steatosis. MRI, MRS, ultrasonography, and CT studies of live patients have correlated different clinical parameters with increased pancreas fat infiltration, including diabetes, BMI/obesity, heavy alcohol use, metabolic syndrome, increased age, hypertension (HTN), visceral adipose tissue, race/ethnicity, waist circumference, male sex, dyslipidemia, and hyperglycemia . In particular, BMI has had mixed results regarding its relationship with pancreas fat quantified by imaging.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, NAFPD has been characterized and associated with diminished pancreatic function and elevated risk of diabetes mellitus (22,43). A large cross-sectional study found that fatty pancreas was present in 35% of patients presenting for a medical check-up, demonstrating its prevalence (18).…”
Section: Discussionmentioning
confidence: 99%